2015
DOI: 10.11648/j.cmr.20150402.13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment the Prevalence of Pulmonary Tuberculosis Patients at Yirga Cheffe Health Center from 2008-2013, Ethiopia

Abstract: Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), is one of the world's most devastating human pathogens that cause more than 2 million deaths annually. In addition, an estimated 2 billion people are latently infected with M. tuberculosis. Ethiopia is ranked 7 th among TB burden shouldering countries in the world. The data collection was carried out typically by secondary data source from already recorded document. The data was obtained from the data clack of pulmonary tuberculosis patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The study revealed that the prevalence of smear-positive TB among different gender (more in males), age groups (more in 25–44 and 65–74 years), educational background (more among lower level of education), family history (more among married), and employment status (more among unemployed). Different studies in Ethiopia have also indicated differences in prevalence of smear-positive TB among different gender and age groups [ 12 14 ], education [ 15 ], employment [ 16 ], and economic status [ 17 ]. Like other studies [ 18 ], in this study, the highest prevalence rate was observed in age group within 25–44 and 65–74, but the prevalence rate was very low in the age groups of 0–14 and 45–64.…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed that the prevalence of smear-positive TB among different gender (more in males), age groups (more in 25–44 and 65–74 years), educational background (more among lower level of education), family history (more among married), and employment status (more among unemployed). Different studies in Ethiopia have also indicated differences in prevalence of smear-positive TB among different gender and age groups [ 12 14 ], education [ 15 ], employment [ 16 ], and economic status [ 17 ]. Like other studies [ 18 ], in this study, the highest prevalence rate was observed in age group within 25–44 and 65–74, but the prevalence rate was very low in the age groups of 0–14 and 45–64.…”
Section: Resultsmentioning
confidence: 99%